2007
DOI: 10.1093/ndt/gfm491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome in a cohort of paediatric patients with membranous lupus nephritis

Abstract: Background. Membranous glomerulopathy accounts for 28% of the biopsy-proven systemic lupus erythematosus nephritis in paediatric patients at the time of first biopsy, yet minimal data are available regarding outcomes in this population. Methods. We present a retrospective analysis of 26 paediatric patients with World Health Organization class V lupus nephritis. Patients were subdivided based on renal biopsy findings into the following subclasses: 16 (63%) Va, 2 (9%) Vb, 7 (26%) Vc and 1 (4%) Vd. We evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This statistic highlights the risk of poor renal outcome for patients with pure class V LN, which has been reported elsewhere. 2,9,[12][13][14][15] This risk may explain the use of more-aggressive treatment for patients with pure MLN, even in the absence of nephrotic-range proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statistic highlights the risk of poor renal outcome for patients with pure class V LN, which has been reported elsewhere. 2,9,[12][13][14][15] This risk may explain the use of more-aggressive treatment for patients with pure MLN, even in the absence of nephrotic-range proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although outcomes for pure class V LN are generally thought to be favorable, renal insufficiency and end-stage renal disease (ESRD) do occur, with reported rates of ESRD ranging from 3% to 28% across adult studies and 0% to 25% in pediatric studies. 2,4,9,[11][12][13][14][15][16][17][18][19] Reliable predictors of ESRD for patients with pure class V LN have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…23 Membranous LN (class V) is a less common form of LN, but some studies have found that its impact is almost as high as diffuse proliferative LN. 24,25 Treatment Most therapies for LN are based on trials conducted in adults rather than in children, as more adults are affected and thus available for study. To date there are no large and comprehensive singlecenter studies in children with LN because of the relatively small sample sizes available.…”
Section: Histopathology Of Lnmentioning
confidence: 99%
“…MN can manifest in a clinical setting of lupus nephritis, hepatitis B, Epstein Barr virus and others [1, 6, 7, 8]. Other rare causes have been described including C4 complement deficiency and antitubular basement membrane antibodies [9].…”
Section: Introductionmentioning
confidence: 99%